'n Strategiese en operasionele beoordeling van die Suid-Afrikaanse Weermag (SAW) se oorgrens-operasies in Angola, 1978-1988 - Scholtz, Leopold (Faculty of Humanities, University of the Free State, 2009)
The cross-border operations of the South African Army between 1978 and 1988 were politically extremely controversial. There were several reasons why the Army undertook them. On a security-strategic level the South African government wanted to prevent SWAPO, a Marxist-Leninist organisation, to seize power in South West Africa (now Namibia). On military-strategic level it was meaningful to take the initiative and disrupt SWAPO before its insurgents could cross the border to South West Africa; also to support UNITA in order to prevent SWAPO from infiltrating the Okavango and West Caprivi. These cross-border operations were successful in the sense that they prevented insurgency and helped to undermine SWAPO’s morale. In the end SWAPO ruled Namibia; the country, however, did not become a Marxist-Leninist dictatorship but a more or less libaral democracy.
Keywords: South African Army; South African government; Cross-border operations; Insurgency; Liberal democracy